PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN JASA SUBSEKTOR PERDAGANGAN ECERAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2015-2020 - Hidayati, Dewi Fortuna; Yuneline, Mirza Hedismarlina (STIE Ekuitas, 2022)
This study was conducted to examine the effect of Current Ratio (CR), Debt to Equity Ratio (DER) on financial distress in retail trading sub-sector service companies listed on the Indonesia Stock Exchange for the 2015-2020 period. In this study financial distress is calculated using the Altman Z-Score method. The research method used is descriptive and verification methods through a quantitative approach using the classical assumption test hypothesis testing design, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, T test and F test. The data is obtained from retail trade sub-sector service companies which from 2015-2020 are listed on the Indonesia Stock Exchange (IDX), the calculation uses statistical methods assisted by the statistical data processing program SPSS 26 version (Statistics of Social Science Program). The results of this study indicate that the current ratio has a positive and significant effect on financial distress and the debt to equity ratio has a negative and significant effect on financial distress. The current ratio is estimated to be 76.9% while the remaining 23.1% is influenced by other factors not examined in this study.